Fintech Waqf for MSMEs Empowerment in Indonesia - Muannasa, Aulia (Institut Agama Islam Negeri Kendari, 2022)
This research suggests that the cash waqf model with a crowd-funding platform in a business project can empower MSMEs to advance the Indonesian economy. This study uses a qualitative approach which is descriptive research. This research describes Sharia Financial Technology (SFT) as a means of integrating solutions to empower MSME companies developed by youth on a waqf basis. The data collection utilizes a literature study from relevant literature such as books, journals or scientific articles related to the chosen topic. The study results show that cash waqf schemes and crowd-funding schemes have helped Islamic banks with speed and accuracy in processing business operation data and product marketing. This finding means that for MSMEs, the existence of Fintech helps to get convenience and efficiency in finance and capital. The implication is that waqf fintech helps develop the community's economic welfare through empowerment, especially for MSMEs. Furthermore, the existence of cash waqf with crowd-funding innovation is very easy for prospective waqifs to make cash waqf.